Asia's energy trends and developments - Hong, Mark; Lugg, Amy V. R. (Singapore : World Scientific, 2013)
'With Asia--especially China and India--leading world energy consumption, Asian energy trends are now of global interest, with deep implications for the world economy and geopolitics. Understanding the issues often require real-life case scenarios. This two-volume compilation presents the key topics on Asia's energy trends and developments that were presented at the Institute of Southeast Asian Studies in Singapore as part of its Energy Series Programme. A wide range of topics is covered, from nanotechnology, clean energy, hydropower, renewable energy and nuclear power to bilateral relations, energy security and energy efficiency--all with the unifying energy theme in the context of Asia'--
vol. 1. Innovations and alternative energy supplies -- vol. 2. Case studies in cooperation, competition and possibilities from Central, Northeast and South Asia.
Includes bibliographical references and index.
Keywords: Power resources -- Asia; Energy development -- Asia; Energy policy -- Asia